Novel hardware for temperature-jump DNP - Breeds, Edward (2018)
Although NMR is a versatile technique, the low values associated with nuclear spin polarization provide inherently weak signals. A novel system to perform temperature-jump dynamic nuclear polarization (DNP) has been designed and developed at the University of Nottingham, with the aim to enhance this signal and improve the sensitivity of the NMR experiment.